Vertical land motion due to present-day ice loss from Greenland’s and Canada’s peripheral glaciers ... - Berg, Danjal Longfors; Barletta, Valentina; Hassen, Javed; Lippert, Eigil; Colgan, William; Bevis, Mike; Steffen, Rebekka; Khan, Shfaqat (Dryad, 2023)
Greenland's bedrock responds to the ongoing loss of ice mass with an elastic vertical land motion (VLM) that is measured by Greenland's GNSS Network (GNET). The measured VLM also contains other contributions, including the long-term viscoelastic response of the Earth to previous deglaciation. Greenland’s ice sheet (GrIS) is producing the most significant contribution to the total VLM. The contribution of peripheral glaciers (PGs) from both Greenland (GrPGs) and Arctic Canada (CanPGs) has not been carefully accounted for in the GNSS time series analysis. This is a significant concern, since GNET stations are often closer to PGs than to the ice sheet. We find that PGs produce significant elastic rebound, especially in North and East Greenland. Across these regions, the PGs result in up to 37% of the elastic rebound. For a few stations in the North, the VLM from PGs is larger than the GrIS one. ... : We estimate daily GNSS site coordinates using the GipsyX software package version GipsyX-2.0 developed at the Jet Propulsion Laboratory (JPL) and released in December 2019 (Landerer et al., 2020). We use JPL final orbit products, which include satellite orbits, satellite clock parameters, and Earth orientation parameters. The orbit products take the satellite antenna phase center offsets into account. The atmospheric delay parameters are modeled using the Vienna Mapping Function 1 (VMF1) with VMF1grid nominals (Boehm et al., 2006). Corrections are applied to remove the solid Earth tide and ocean tidal loading. The amplitudes and phases of the main ocean tidal loading terms are calculated using the Automatic Loading Provider (http://holt.oso.chalmers.se/loading/) applied to the FES2014b ocean tide model (Carrère et al., 2016), including correction for the center of mass motion of the Earth due to the ocean tides. The site coordinates are computed in the IGS14 frame (Altamimi et al., 2016). We estimated ...